MEASURING ENVIRONMENTAL COSTS IN APPLICATION OF SUSTAINABLE DEVELOPMENT STANDARDS TO IMPROVE THE FINANCIAL PERFORMANCE OF COMPANIES - Mithal Kreem Kadhim Al-Zubady (Scholar Express Journals, 2024)
The research aims to show the impact of social responsibility in industrial companies and their role in improving financial performance using one of the dimensions of sustainable development (environmental standard), and a sample represented by  Company (X) for  the production of mineral water in Baghdad has been withdrawn within the community of companies contributing to the Iraqi market to study the data of its financial statements and social responsibility reports for the year 2019 in addition to conducting some special interviews with factory managers and benefiting from the information that serves our current research after responding For their request that the name of the company remain unannounced, financial indicators have been used: net profit ratio, debt ratio, trading ratio, and a set of conclusions were reached, the most important of which is the absence of separate reports on social responsibility, while there are initiatives towards social responsibility, which negatively affects the improvement of its financial performance and thus the non-implementation of sustainable development programs, one of the most important recommendations is the need to pay attention to social responsibility in order to improve its financial performance as a step in investing in social responsibility and supporting sustainable development.
Keywords: Social responsibility, sustainable development, environmental criterion, financial performance, measurement of environmental costs